2021
DOI: 10.3389/fendo.2021.680328
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From M2 Macrophages Facilitate Osteogenesis and Reduce Adipogenesis of BMSCs

Abstract: Bone regeneration is a complex process that requires the coordination of osteogenesis and osteoclastogenesis. The balance between osteogenesis and adipogenesis of bone marrow mesenchymal stem cells (BMSCs) plays a major role in the process of bone formation. Recently, intercellular communication between bone cells and surrounding cells has been gradually recognized, and macrophages on the surface of bone have been proven to regulate bone metabolism. However, the underlying mechanisms have not been fully elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 46 publications
1
45
0
1
Order By: Relevance
“…These findings indicate that EVs from the same phenotype Mφ have different effects on the osteogenic differentiation of BMSCs. M2-EVs increased the expression of miR-690, IRS-1, and TAZ in BMSCs, inhibiting adipogenesis and promoting osteogenesis of BMSCs [25]. EVs with complex cargos have been suggested to play different roles in BMSC differentiation.…”
Section: Effect Of Mc-mφ-derived Evs On Osteogenesismentioning
confidence: 99%
“…These findings indicate that EVs from the same phenotype Mφ have different effects on the osteogenic differentiation of BMSCs. M2-EVs increased the expression of miR-690, IRS-1, and TAZ in BMSCs, inhibiting adipogenesis and promoting osteogenesis of BMSCs [25]. EVs with complex cargos have been suggested to play different roles in BMSC differentiation.…”
Section: Effect Of Mc-mφ-derived Evs On Osteogenesismentioning
confidence: 99%
“…4 Researchers found that there was a relative balance between osteogenic and adipogenic differentiation of MSCs. 5 When the adipogenesis increased, the transferring of MSCs to osteoblasts would decrease which led to bone mass loss. 6 Additionally, some clinical studies demonstrated the phenomenon that the fat fraction was inversely proportional to the bone mineral density of the lumbar vertebra.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes secreted by osteoblasts inhibit the differentiation of osteoclast progenitor cells (Wang Q. et al, 2021). Exosomes derived from M2 macrophages (M2D-Exos) inhibit adipogenesis and promote osteogenesis of BMSCs (Li Z. et al, 2021). Therefore, Nan et al constructed exosomes from miRNA-378-transfected adipose-derived stem cells (ASCs) and cocultured the extracted exosomes with BMSCs and human umbilical vein endothelial cells (HUVECs).…”
Section: Other Types Of Methods To Transfect Mirna Into Cellsmentioning
confidence: 99%